Regulation of stemness and differentiation in colorectal cancer - Gandhi, S (2010)
The cancer stem cell (CSC) model of carcinogenesis and progression posits that within a tumor lies a subpopulation of cells that solely possess the ability to initiate a tumor and to differentiate into tumor cell lineages. Although the behavior of such cells is known, the challenge is to identify factors that characterize the CSC subpopulation. In this thesis, cell lines were identified that, when grown in three-dimensions, gave rise to organized colonies containing lumens originating from differentiating cells (“lumen lines”) and to densely-packed, spherical colonies originating from non-differentiating cells (“dense lines”). A microarray comparison of the pair identified genes upregulated in dense lines, including CD55 and BMI1, and in lumen lines, including CDX1 (Chapter 3). CD55 was used to isolate CD55high CSCs via flow cytometry that are able to self-renew, differentiate, initiate more colonies, proliferate more rapidly and exhibit an increased G2/M cell cycle population as opposed to unfractionated cells. Furthermore, the CD55high cells were able to give rise to more differentiated, lumen colonies in vitro, indicating that CD55 enriches for cells possessing a capacity to differentiate, and were able to enrich the CD24highCD44high putative CSC population further (Chapter 4). CDNA induction of BMI1 and CDX1 expression led to increased clonogenicity/proliferation and decreased clonogenicity/proliferation, respectively, and incorporation of a CDX1 reporter construct into the SW1222 cell line identified CDX1+ cells as a low-expressing population of CD55 (Chapter 5). Finally, co-culture of cell lines in an in vivo-like environment with intestinal myofibroblasts promoted the CSC population by enhancing clonogenicity, proliferation and expression of CD55 (Chapter 6). The results of this thesis implicate CD55 as a potent marker of colorectal cancer stemness, link the expression of BMI1 and CDX1 to cancer stemness and differentiation, respectively, and identify a role for the in vivo stem cell niche in maintaining the CSC population.